PENGARUH LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA DAN IMPLIKASINYA TERHADAP KINERJA KARYAWAN DI PERGURUAN TINGGI SWASTA STIMART-AMNI SEMARANG - Tri Winarno (STIE Pelita Nusantara Semarang, 2012)
The objective of this research is to prove the influence of work surroundings and leadership style toward work motivation and the implication toward employee work in Semarang STIMART-AMNI college. To do this research, it will be needed the theory related to the definition of human resources management, the definition of work surroundings, surroundings factors, the definition of work and work system. The location of this research is in Semarang STIMART-AMNI College. The method done to collect sample is sensus, which all population become sample because the population is less than 100. The sample of total is 65 people. Data analysis used is the experiment of validity, reliability, and bifilar regression, and also simple regression. The result oh the study can be concluded that variable used together in this research, those are work surroundings and leadership style, give the influence toward employee work motivation. Next, simple motivation variable simple can influence the work system of the employee in Semarang STIMART-AMNI College.